Designing UI/UX for CareerSite Website Using LeanUX Method - Najib, Mochammad; Trafika, Evania (Information Technology International Journal, 2023)
One of the causes of the increasing number of unemployed in Indonesia is due to fresh graduates who do not have sufficient information about careers so they are still unsure about choosing a job that suits their interests. Based on these problems, a CareerSite website was created which will equip the community in choosing and developing their interests and talents according to the job they want. Creating a CareerSite website interface design will make it easier for the public to develop their interests and talents. The research method used in this research is using LeanUX and with Usability Testing. 10 respondents were taken to try the prototype from the CareerSite website then continued to provide an assessment and feedback through a questionnaire. The results obtained from usability testing using the UEQ-S obtained a scales value on the pragmatic quality aspect of 1.900 and on the hedonic quality value aspect of 0.925. 60% of respondents stated that the appearance of the CareerSite website is efficient, fun and creative when used. Feedback obtained from respondents can be used as further research to develop this CareerSite website better.